Circulating tumor cells in early bladder cancer: insight into micrometastatic disease. (May 2014) - Raimondi, Cristina; Gradilone, Angela; Gazzaniga, Paola
<x xml:space="preserve">Abstract</x> Although several studies have demonstrated the prognostic and predictive potential of circulating tumor cells (CTCs), to date their evaluation still has not impacted the treatment strategy. There is wide consensus that CTC assessment would be more beneficial in early stage cancer, especially in those tumor types characterized by early progression and a lack of prognostic markers. Non-muscle-invasive bladder cancer represents an optimal model to this purpose. In fact, the rate of metastatic spread ranges between 20 and 40%, which is unacceptable for a 'superficial' tumor and unexpected in an early stage cancer. This may be due to the presence of non-clinically detectable micrometastases. CTCs may be used as a noninvasive, real-time tool for the stratification of early stage bladder cancer patients according to individual risk of progression.